The importance of events, happiness and brand love for a place sustainability - Dutschke, J.; Dutschke, G.; Dias, Á.; Pereira, L. F. (International Journal of Business and Emerging Markets, 2024)
This study aims to understand to what extent effective events contribute to the image of the city that receives them, promoting the love of the city-brand and positively influence the happiness of the inhabitants and non-inhabitants. A case study was lead in the city of Cascais, using two events, 'Estoril Open' and 'Festas do Mar - Cascais'. The surveys, based on validate models of event efficacy, brand love and happy cities, were applied in two distinct samples, one composed by the inhabitants of Cascais and the other by non-inhabitants. By testing hypothesis and through correlation analysis, was concluded that effective events contribute to the image of the host city, promoting the love of the city-brand and positively influencing the happiness of the inhabitants and not inhabitants.